Pragmatic Strategy of Indonesian English Teachers in Questioning - Hieronimus Canggung Darong (Yayasan Visi Intan Permata, 2020)
This study was an attempt to examine pragmatic strategies and questioning types employed by English teachers in classroom interactions. Delivering the functions of questions by their types is insufficient to manage the flow of interaction. As such, the teachers need a certain pragmatic strategy. Data were gathered from three Indonesian English teachers. Purposefully selected teachers were observed, audio-recorded, and analyzed by using Gricean cooperative principle and politeness principle following the principle of Conservation Analysis (CA). The conservation analysis revealed that the use of external devices- adjunct to the head acts or enquirers (grounder, sweetener, and disarmer) and internal modifiers (syntactic interrogative downgraders and lexical consultative downgraders) were mostly used by the teachers in employing questions to mitigate the illocutionary act of questioning as a request. In addition, the teachers intentionally violated the maxim for the sake of managing the flow of conservation. Subsequently, this study mirrors previous research findings that display questions as the most frequent strategies used to extend the talk and to invite learner response. Instead of analyzing questions that conventionally associate those with speech act theory, social aspects of interpersonal normativity (being responsible and autonomous) might be of benefit in sharing social-communicative intentions in order to extend the classroom talk.